Stereocomplexes of Discrete, Isotactic Lactic Acid Oligomers Conjugated with Oligodimethylsiloxanes - Lamers, Brigitte A. G. (Macromolecules, 2019)
[Image: see text] Discrete length block co-oligomers (BCOs) comprised of a crystalline and an amorphous block are a new class of materials that gives highly ordered lamellar morphologies at small length scales. Here, we show the preparation of discrete, isotactic oligo l- and d-lactic acid (olLA and odLA) homoblocks followed by ligation to oligodimethylsiloxane (oDMS), affording a library of crystalline–amorphous BCOs that vary in molecular weight and composition. Mixing the two enantiomeric BCOs or homoblocks results in the formation of the corresponding stereocomplex. The properties and phase behavior of the isotactic (block co)oligomers and the stereocomplexes thereof are studied using differential scanning calorimetry and small-angle X-ray scattering. A systematic study of the isotactic homoblock lengths and crystal structure confirmed the formation of a 10(3) helix with a monomeric rise of 0.3 nm, whereas the stereocomplex adopts a 3(1) helix. The same type of crystal structure was found for the isotactic and stereocomplex of BCOs giving rise to the formation of lamellar morphologies at room temperature as a result of crystallization of the oLA blocks. Distorted lamellar structures were found in BCOs that preorganize into nonlamellar morphologies prior to crystallization. The stereocomplex BCOs shows more crystal defects and a loss of long-range ordering in the microstructure due to the larger driving force for crystallization. Hence, the balance between chain length, block volume, and the crystallization strength are of major importance for the formation of the final structure with the least defects.